The effect of nitrogen, phosphorus and potassium fertilisation on the growth, yield and quality of Lachenalia - Engelbrecht, G. M. (University of the Free State, 2004)
Very little is known about the response of Lachenalia to fertilisation when cultivated in soil. The objective of this study was therefore to quantify the effect of fertilisation on the growth, yield and quality of Lachenalia in both the nursery and pot plant phases. In order to achieve this two pot trials for the nursery phase and one pot trial for the pot plant phase were conducted in the glasshouse. For the first trial in the nursery phase the combined effect of nine nitrogen levels and three application times on the Lachenalia cultivars, Rupert and Ronina, were studied. The nitrogen was applied at levels equivalent to 0, 30, 70, 120, 180, 250, 330, 420 or 520 kg N ha -1 . Three different nitrogen application times were used namely: one third with planting and the rest 10 weeks after planting (T1); one third with planting and the other two thirds after planting (T 2) or one quarter with planting and the other three quarters after planting (T3). The leaf area of Ronina plants was larger than that of Rupert plants irrespective of nitrogen levels and application times. However, Ronina bulbs were larger and softer than Rupert bulbs. The nutrient (N, P, Ca and Mg) and carbohydrate (D-glucose, sucrose and starch) content of Rupert bulbs were higher than that of Ronina bulbs. Application of nitrogen had a positive influence on the leaf area, bulb fresh mass and circumference of both cultivars. Bulb firmness was negatively influenced by nitrogen application. The best results for most parameters were obtained when nitrogen was applied in four equal applications. In the second trial for the nursery phase the response of Rupert and Ronina to five nitrogen (0, 70, 180, 330 or 520 kg N ha -1 ) and five phosphorus (0, 10, 30, 50 or 80 kg N ha -1 ) or five potassium (0, 70, 180, 330 or 520 kg N ha -1 ) levels were studied. Neither the interaction between nitrogen and phosphorus levels nor the interaction between nitrogen and potassium levels had a large influenced on the growth and development of Lachenalia. Results obta ined in this trial with respect to the effect of nitrogen levels on the different parameters mainly confirm with the results obtained with the first trial. In the trial for the pot plant phase the effect of seven nitrogen levels (0, 30, 70, 120, 180, 250, 330, 420 or 520 kg N ha -1 ) on Lachenalia grown from 7-8 cm bulbs, whereof the fertilisation history in the nursery phase differed, was investigated. The fertilisation history of the bulbs in the nursery phase consisted of three nitrogen levels (0, 70, 250 or 520 kg N ha -1 ) combined with two nitrogen application times (T1, T2 or T3 as described earlier). The leaf area of Ronina plants was larger than that of Rupert plants. Nitrogen applied in the nursery phase promoted the leaf area of both Rupert and Ronina. Application of nitrogen in the nursery phase and in the pot plant phase increased the number of inflorescence per plant and the number of florets per inflorescence. The peduncle length increased with higher nitrogen levels in the nursery phase wherea s the peduncle diameter increased with higher nitrogen levels in the pot plant phase.

Min inligting is bekend oor die reaksie van Lachenalia op bemesting wanneer dit in grond verbou word. Die doel van die studie was om die effek van bemesting op die groei, opbrengs en kwaliteit van Lachenalia in beide die kwekery- en potplantfase te kwantifiseer. Om dit te bereik is twee potproewe vir die kwekeryfase en een potproef vir die potplantfase in die glashuis uitgevoer. Vir die eerste potproef in die kwekeryfase is die gekombineerde effek van nege stikstof peile en drie toedienings tye op die twee Lachenalia cultivars, Rupert en Ronina, ondersoek. Stikstof is toegedien teen peile ekwiwalent aan 0, 30, 70, 120, 180, 250, 330, 420 of 520 kgN ha-1. Drie verskillende toedieningstye is gebruik naamlik: een derde met plant en die ander twee derdes tien weke na plant (T 1); een derde met plant en die ander twee derdes na plant deur die groeiseisoen (T2) of een kwart met plant en die ander drie kwarte na plant deur die groeiseisoen (T3). Die blaaroppervlak van Ronina plante was grootter as die van Rupert plante ongeag die stikstofpeile en toedieningstye. Ronina bolle was ook grootter en sagter as die bolle van Rupert. Die voedingstofinhoud (N, P, Ca en Mg) en koolhidraatinhoud (D-glukose, sukrose en stysel) van Rupert bolle was hoër as die van Ronina bolle. Stikstoftoediening het ‘n positiewe invloed op die blaaroppervlak, bolmassa en -omtrek van beide cultivars gehad. Stikstoftoediening het die fermheid van bolle is negatief beïvloed deur stikstoftoediening. Die beste resultate vir die meeste parameters wat gemeet is, is verkry as stikstof in vier gelyke dele (T 3) deur die groeiseisoen toegedien is. In die tweeede proef vir die kwekeryfase is die reaksie van Rupert en Ronina op vyf stikstof - (0, 70, 180, 330 or 520 kgN ha-1) en vyf fosfor- (0, 10, 30, 50 or 80 kg N ha -1) of vyf kaliumpeile (0, 70, 180, 330 or 520 kgN ha-1) ondersoek. Die interaksie tussen stikstof - en fosforpeile asook die interaksie tussen stikstof- en kaliumpeile het nie ‘n groot invloed op die groei en ontwikkeling van Lachenalia gehad nie. Resultate wat verkry is in die proef met betrekking tot die invloed van stikstofpeile op die die groei en ontwikkeling van Lachenalia het grootliks die resultate bevestig wat in die eerste proef verkry is. In die proef vir die potplantfase is die invloed van sewe stikstofpeile (0, 30, 70, 120, 180, 250, 330, 420 of 520 kg N ha-1) op Lachenalia , wat ontwikkel het uit 7-8 cm bolle en waarvan die bemestingsgeskiedenis verskil, ondersoek. Die bemestingsgeskiedenis van die bolle in die kwekeryfase het uit drie stikstofpeile (0, 70, 250 of 520 kg N ha-1) bestaan wat met twee stikstof toedieningstye (T1, T2 of T3 soos vroeër verduidelik) gekombineer is. Die blaaroppervlak van Ronina plante was groter as die van Rupert. Stikstof wat in die kwekeryfase toegedien is het die blaaroppervlak van beide Rupert en Ronina in die potplantfase positief beïnvloed. Die aantal bloeiwyses per plant en blommetjies per bloeiwyse het toegeneem soos die stikstofpeile verhoog het in die kwekery- asook die potplantfase. Die bloeisteellengte verleng met ‘n toename in stikstofpeile in die kwekeryfase terwyl die deursnee van die bloeisteel toeneem met ‘n toename in stikstofpeile in die potplantfase.
Thesis (Ph.D. (Soil, Crop and Climate Sciences))--University of the Free State, 2004
Keywords: Bulb quality; Inflorescence quality; Leaf area; Peduncle length; Florets quality; Lachenalia -- South Africa; Bulbs (Plants) -- Fertilizers -- South Africa